The Assesment of Inclusiveness Principle of Malaysian New Economic Model: Maqashid Syar’iyyah Perspective - Haron, M. Sabri; Rahman, Riki; Possumah, Bayu T. (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2015)
Objective of this article is to assess how far the principles of inclusiveness in the Economic New Model in Malaysia can fulfil the needs of maqasid syar’iyyah. The assessment is conducted through the key concepts and strategic measures of the principles of inclusiveness. This study is a qualitative which descriptive and analytical approach is used for assessing  the  principles  of  inclusiveness  in  the  Economic  New  Model  based  on maqasid  syar’iyyah  perspective.  The  method  of  this  study  is  using  the  literature review  with  references  from  secondary  data.  This  study  is  expected  to  provide recommendations about the important role of maqasid syar’iyyah for maintaining the welfare of society and developing of a country, in this context for developing the Malaysian economy, in line with the vision 2020, Malaysia on par with developed countries.DOI:10.15408/aiq.v7i1.1362